Effectiveness and safety of tuberculin purified protein derivative for the treatment of anogenital warts in patients with human immunodeficiency virus - Pati Aji Achdiat; Stephanie Widjaja; Oki Suwarsa; Reiva Farah Dwiyana; Reti Hindritiani; Endang Sutedja; Hendra Gunawan; Hermin Aminah Usman; Fathia Rianty; Retno Hesty Maharani (PAGEPress Publications, 2024)
Individuals with human immunodeficiency virus (HIV) infection are prone to developing persistent and unremitting anogenital warts (AGWs). To address this health condition, immunotherapy using tuberculin purified protein derivative (PPD) has been proven to be a promising novel and safe treatment for AGWs in HIV patients. Therefore, this study involved a case of a 21-year-old man with stage I HIV infection, possessing CD4 counts 548 cells/uL and routinely receiving HIV antiretroviral. Patients presented with a condyloma acuminata type AGWs, supported by histopathological results, and tested positive for Human papillomavirus type 11. The treatment approach involved administering 15 tuberculin units of PPD weekly to the largest lesion for 5 weeks. The lesion started to respond two weeks following the first injection and showed a 50% decrease in size after five weeks. There was pain on the site of injection and sub-febrile for a short period. In conclusion, tuberculin PPD is safe and has the potential for the treatment of AGWs in HIV-positive patients for further development.